2013
DOI: 10.1155/2013/365194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hay’s Criteria with Nugent’s Scoring System for Diagnosis of Bacterial Vaginosis

Abstract: Although Nugent's criterion is considered as the gold standard for the diagnosis of bacterial vaginosis (BV), the method requires an experienced slide reader and considerable time and skill. In this study, we compared the method of Hay and Ison with Nugent's scoring criteria. Vaginal specimens were collected from a total of 213 women, presenting with or without the symptoms of vaginitis. Diagnosis of BV was done using Nugent' and Hay's method. Sensitivity, specificity, and predictive values for positive and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
(22 reference statements)
3
17
0
3
Order By: Relevance
“…Only 10.4% of the participants displayed intermediate microbiota in our study set. Similar results were also obtained in other studies 36 , 38 , 39 . However, several studies have reported higher rates of intermediate microbiota in women 44 46 , showing rates between 36.3 and 69.2%.…”
Section: Discussionsupporting
confidence: 92%
“…Only 10.4% of the participants displayed intermediate microbiota in our study set. Similar results were also obtained in other studies 36 , 38 , 39 . However, several studies have reported higher rates of intermediate microbiota in women 44 46 , showing rates between 36.3 and 69.2%.…”
Section: Discussionsupporting
confidence: 92%
“…There is a low level of estimation in our study when compared to other studies (Rohit Chawla et al, 32.86% and Modak T et al, 24%). 16,17 Since only laboratory method was employed, correlation between Amsel criteria method and Nugent scoring method could not be obtained in our study. The consequences of BV include abortion, still birth; preterm deliveries and co infections are also more common.…”
Section: Discussionmentioning
confidence: 84%
“…Clinical laboratories identify changes in the vaginal environment through microscopic examination and vaginal swab culture (Hong et al, 2016 ). Nugent scoring involves Gram-staining of vaginal smears and has been suggested as the gold standard in the diagnosis of BV in comparison to Amsel's criteria, which is based on non-quantifiable, non-reproducible clinical symptoms only (Chawla et al, 2013 ; Amegashie et al, 2017 ; Antonucci et al, 2017 ; Coleman and Gaydos, 2018 ). The diagnosis of BV is made on quantification of the Gram-stained microorganisms, classifying these organisms based on different vaginal morphotypes as well as the identification of clue cells (part of the Amsel's criteria) which could be laborious and requiresskilled personnel (Nugent et al, 1991 ; Chawla et al, 2013 ; Antonucci et al, 2017 ).…”
Section: Current Diagnostic Avenuesmentioning
confidence: 99%